Millennials' and Z Generation's Knowledge on Child Immunization and the Role of Media in the Digital Era in Jabodetabek, Indonesia - Della Sabrina Marta MD; Ellen Wijaya MD (SAGE Publishing, 2023)
Vaccine hesitancy is a threat for global health. Shortly, millennials and Z generation (gen-Z), the digital natives, are responsible for the future of the children. No study was found yet regarding child immunization and the usage of media in Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek), Indonesia. This study aim to determine factors affecting millennials' and Z generation's knowledge about child immunization and the usage of media as the source of health information. Online questionnaire was distributed from 25 th September to 20 th November 2020 to students and workers in Jabodetabek. Subjects with child and/or <15 or >40 years old are excluded. Analysis was done with SPSS 20. Total of 376 subjects with mean age 18 (15-38) years old were collected. Subject's varies from high school students (48.4%), university students (46.2%) and workers (1.6%). Total of 357 (94.9%) subjects willing to complete their future child's immunization. Internet was the primary source of health information for 357 (94.9%) subjects, especially Instagram for 129 (34.3%) subjects. Concluded that subjects' immunization status affects their willingness to fully vaccinate their future children. Digital media (Instagram) is the primary source of health information. Educational background affects their consideration in trusting online sources